ANALISIS SUMBER DAN PENGGUNAAN KAS PADA PT. CEMINDO GEMILANG, Tbk. - Amir, Ilmy Dzauqy Kasyfiah; Irmawati, Irmawati (Universitas Patria Artha, 2023)
The problem in this research is how the company's cash source PT. Cemindo Gemilang Tbk., use of cash PT. Cemindo Gemilang Tbk., and analysis of the sources and use of cash at PT. Cemindo Gemilang Tbk. year 2019-2021. The research method used in this research is descriptive with a quantitative approach. The subjects in this study were PT. Cemindo Gemilang Tbk. Listed on Bursa Efek Indonesia. This study uses secondary data in the form of financial statements of PT. Cemindo Gemilang Tbk. period 2019-2021 obtained from the official website of the Bursa Efek Indonesia. The results of this study indicate that the analysis of sources and use of cash at the company PT. Cemindo Gemilang Tbk. in 2019 and 2020 it can be said that the financing/spending structure carried out by the company is not appropriate, because according to the liquidity view, the company's long-term needs are met by short-term funding sources. Meanwhile, in 2021, it can be said that the financing/spending structure carried out by the company is correct, because according to liquidity there is no need for longterm funds to be financed with short-term sources of funds, and short-term funding needs are met with short-term sources.